Injury-specific pathways shape corneal nerve regeneration dynamics - Léna Meneux; Sarah Pernot; Nadège Feret; Melissa Girard; Alicia Caballero Megido; Marilou Decoudu; Naima Nhiri; Elea Miessen; Eric Jacquet; Vincent Daien; Frederic Michon (Scientific Reports)
Abstract The cornea, a transparent tissue critical for clear vision, is uniquely characterized by a dense network of peripheral sensory nerves. This innervation not only enables sensation but also provides vital trophic support, ensuring corneal health and integrity. Damage or loss of these peripheral nerves leads to neurotrophic keratitis (NK), a debilitating condition that disrupts corneal healing and function, ultimately threatening vision. Remarkably similar to other peripheral neuropathies, NK arises from various injuries, diseases, or surgical interventions, yet its underlying regenerative mechanisms remain poorly understood, limiting effective treatment options. In this study, we investigated how corneal nerves regenerate following two different types of clinically relevant injuries—axotomy (mimicking nerve damage during corneal transplantation) and epithelial abrasion (resembling superficial corneal surgery). We found that the type of injury distinctly influences both the structural and functional recovery of corneal nerves. Axotomy resulted in delayed nerve regeneration, significant disruption of epithelial cell homeostasis, and increased risk of severe corneal damage. Conversely, epithelial abrasion induced rapid but structurally abnormal nerve recovery. Furthermore, we identified specific molecular pathways activated differently depending on injury type. Our findings highlight the complexity of peripheral nerve regeneration, underscoring the necessity for targeted therapeutic strategies tailored to individual injury scenarios. By illuminating the variability in nerve recovery, our study provides valuable insights applicable not only to NK but potentially to a broader spectrum of peripheral neuropathies, paving the way for novel therapeutic interventions.